Workers' tenure and firm productivity: New evidence from matched employer‐employee panel data. Issue 1 (28th April 2022) - Gagliardi, Nicola; Grinza, Elena; Rycx, François
Abstract: Using rich longitudinal matched employer‐employee data on Belgian firms, we explore the impact of workers' tenure on firm productivity. To do so, we estimate production functions augmented with firm‐level measures of tenure. We deal with the endogeneity of standard inputs and tenure, which arises from unobserved firm heterogeneity and reverse causality, by applying a modified version of Ackerberg et al.'s (2015) control function method, which explicitly removes firm fixed effects. Consistently with recent theoretical predictions, our analyses point to positive, but decreasing, returns to tenure. We also find that the impact differs widely across several firm dimensions. Tenure is particularly beneficial for productivity in contexts characterized by a certain degree of routineness and low job complexity. Along the same lines, our findings indicate that tenure exerts stronger positive impacts in industrial and capital‐intensive firms, as well as in firms less reliant on ICT‐intensive and knowledge‐intensive processes.